Somatic Clonal Analyses Using FLP/FRT and MARCM System to Understand Notch Signaling Mechanism and Its Regulation. - Sharma, V.; Sachan, N.; Mutsuddi, M.; Mukherjee, A. (Methods in molecular biology (Clifton, N.J.), 2022)
Notch signaling regulates an array of developmental decisions and has been implicated in a multitude of diseases, including cancer over the past a few decades. The simplicity and versatility of the Notch pathway in Drosophila make it an ardent system to study Notch biology, its regulation, and functions. In this chapter, we highlight the use of two powerful techniques, namely, FLP/FRT and MARCM in the study of Notch signaling. These mosaic analysis techniques are powerful tools to analyze gene functions in different biological processes. The section briefly explains the principle and the protocols with suitable examples.